Simulating Strategies for Improving Control of Hypertension Among Patients with Usual Source of Care in the United States: The Blood Pressure Control Model - Fontil, Valy; Bibbins-Domingo, Kirsten; Kazi, Dhruv S.; Sidney, Stephen; Coxson, Pamela G.; Khanna, Raman; Victor, Ronald G.; Pletcher, Mark J. (Journal of general internal medicine : JGIM, 2015)
ABSTRACT BACKGROUND Only half of hypertensive adults achieve blood pressure (BP) control in the United States, and it is unclear how BP control rates may be improved most effectively and efficiently at the population level. OBJECTIVE We sought to compare the potential effects of system-wide isolated improvements in medication adherence, visit frequency, and higher physician prescription rate on achieving BP control at 52 weeks. DESIGN We developed a Markov microsimulation model of patient-level, physician-level, and system-level processes involved in controlling hypertension with medications. The model is informed by data from national surveys, cohort studies and trials, and was validated against two multicenter clinical trials (ALLHAT and VALUE). SUBJECTS We studied a simulated, nationally representative cohort of patients with diagnosed but uncontrolled hypertension with a usual source of care. INTERVENTIONS We simulated a base case and improvements of 10 and 50 %, and an ideal scenario for three modifiable parameters: visit frequency, treatment intensification, and medication adherence. Ideal scenarios were defined as 100 % for treatment intensification and adherence, and return visits occurring within 4 weeks of an elevated office systolic BP. MAIN OUTCOME BP control at 52 weeks of follow-up was examined. RESULTS Among 25,000 hypothetical adult patients with uncontrolled hypertension (systolic BP ≥ 140 mmHg), only 18 % achieved BP control after 52 weeks using base-case assumptions. With 10/50 %/idealized enhancements in each isolated parameter, enhanced treatment intensification achieved the greatest BP control (19/23/71 %), compared with enhanced visit frequency (19/21/35 %) and medication adherence (19/23/26 %). When all three processes were idealized, the model predicted a BP control rate of 95 % at 52 weeks. CONCLUSION Substantial improvements in BP control can only be achieved through major improvements in processes of care. Healthcare systems may achieve greater success by increasing the frequency of clinical encounters and improving physicians’ prescribing behavior than by attempting to improve patient adherence to medications.